Banjo - Evans, Bill, 1956- (--For dummies., 2020)
"Join the banjo revolution! Thanks to its prevalence in folk and bluegrass, the banjo is almost the very essence of Americana. And now a new generation of musicians from the country, pop, and jazz worlds have made the sound of the banjo new again. This book is for anyone who wants to pay their respects to tradition as well as those who want to create the next chart-topper ... or both! Packed with the essentials you need to know--from top techniques to choosing the right instrument--you'll learn, and be able to show off, just why the banjo is never out of style!" -- Amazon.com.